Effect of Beauveria bassiana and Metarhizium anisopliae on the coffee berry borer parasitoid Cephalonomia stephanoderis - REYES-ARISTIZÁBAL, INDHIRA CRISTINA; BUSTILLO-PARDEY, ALEX ENRIQUE; CHAVES-CÓRDOBA, BERNARDO (Revista Colombiana de Entomología, 1995)
Experiments carried out to study the effect of the entomopathogenic fungi Beauveria bassiana (isolate Bb9205) and Metarhizium anisopliae (isolate Ma9101) on Cephalonomia stephanoderis, a parasitoid of the coffee berry borer, Hypothenemus hampei, under laboratory conditions (R.H.=90%; T=23.4 ± 1°C) demonstrated that both fungi (10' conidia/ ml) applied directly killed 48% and 40% of parasitoids respectively. In subsequent field trials, in the Experimental Station "La Catalina" (1,340 mas!; T=21.9°C; R.H.= 80.9%), coffee branches, previously infested artificially into entomological sleeves, were sprayed with the fungi (7.9 x 109conidia/tree) according to the following treatments: 21, 14, 7 and O days before parasitoid release, and 2, 4, and 7 days after parasitoid release. The highest mortality (24% B. bassiana, 5% M. anisopliae) occurred when the fungi were sprayed on the same day that parasitoids were released. In all other treatments, the mortality was less than 7% and was not significantly different from the control. Results indicate than the fungi are compatible with the adult parasitoid and can be used in an IPM programme though fungal sprays should not be carried out shortly before or after parasitoid release.